MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN MATERI HAK DAN KEWAJIBAN MELALUI PENERAPAN STRATEGI TRUE OR FALSE - Neneng Suryanah, Yeni Sulaeman, Tatu Maesaroh (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This research aims to determine the improvement in student learning outcomes and the process of implementing true or false strategies in Civics subjects regarding rights and obligations. The method used is classroom action research carried out through 2 cycles with stages: planning, action, observation and reflection. The research subjects were 30 class IV students. The results of the research show that the true or false strategy can improve student learning outcomes in Civics subjects, rights and obligations in class IV at SDN Labuan 3, Labuan subdistrict, Pandeglang district. This can be seen from the level of student learning completion per cycle, namely in the pre-cycle it was only 23. 33%, cycle I 53.33% and cycle II reached 86.67%.